Different Gelation and Self‐Sorting Properties of Two Isomeric Polyamides Owing to the Parallel versus Anti‐Parallel Alignment of Backbone Dipoles. Issue 20 (21st March 2017) - Leung, Chui‐Fan; Chow, Hak‐Fun
Abstract: Two isomeric bottlebrush polyamidesP‐1 andA‐1, with the same repeating monomer dipole units aligned along the polymer backbone in pseudo‐parallel and pseudo‐antiparallel fashion, respectively, were synthesized and characterized. Both polymers can form thermoreversible gels with aromatic solvents butP‐1 was found to show inferior gelation strength compared with that ofA‐1 . Furthermore, despite their close structural resemblance, a 1:1 mixture of theP‐1 andA‐1 polymers was shown to exhibit self‐sorting in the gel state. Gel formation was found to be a kinetically trapped process through hydrogen bonding, π–π stacking interactions, and side chain interdigitation. The different gelation and self‐sorting properties can be explained by the local dipole–dipole interactions originating from the different modes of backbone dipole alignment. In single gel systems, the antiparallel‐aligned dipoles inA‐1 facilitated a more compact molecular packing owing to the enthalpically more favorable polymer chain association. On the other hand, the parallel‐aligned dipoles inP‐1 gave rise to a less stable head‐to‐head packing, which had difficulties to convert to the more stable head‐to‐tail packing in a kinetically trapped environment. In the mixed gel system, it is the unfavorable hetero‐polymer mismatch dipole–dipole interaction that inhibited the mixing of theA‐1 andP‐1 polymers and led to self‐sorting. Abstract : Aligning the spine : Two isomeric polyamides, one with the backbone dipoles aligned in antiparallel and the other in parallel fashion, were found to show different organogelation properties. They also exhibited self‐sorting in their 1:1 mixed toluene gel. These observations can be rationalized by the different local dipole–dipole interactions manifested in the pure gel and the mixed gel systems (see figure).